Concurrent validity of the depression and anxiety components in the Bahasa Malaysia version of the Depression Anxiety and Stress Scale (DASS) - Musa, Ramli; Ramli, Roszaman; Abdullah, Kartini; Sarkarsi, Rosnani (ASEAN Federation of Psychiatry, 2011)
Objectives: The Bahasa Malaysia (BM) version of Depression Anxiety Stress Scales 21-item (DASS-21) has been widely used ever since the establishment of its validity. To consolidate the evidence of the BM DASS-21 validity by examining its concurrent validity. Methods: The BM DASS was administered together with the Hospital Anxiety and Depressive Scale (HADS) to a total of 246 patients at International Islamic University Malaysia (IIUM) Infertility Centre. Results: The anxiety domain of BM DASS-21 had good correlation with anxiety domain in HADS (0.61) but for DASS depressive domain, it had modest correlation with its respective domain in HADS (0.49). Conclusions: The results of this study further ensconced the evidence that the BM DASS-21 had relatively satisfactory psychometric properties for clinical subjects in Malaysia. ASEAN Journal of Psychiatry, Vol.12(1), Jan – June 2011: XX XX.